Language Learning at Natural Disaster Area in Elementary Schools - Muzaki, Ferril Irham (Lingual Journal of Language and Culture, 2019)
Abstract One of the challenges in designing language learning in elementary schools is the ability to predict the skills of learners. To meet this need the Ministry of Education and Culture in designing the national exam which is one of the standardized tests in Indonesia. The use of multiple choice in national exams has an efficient basis for the correction of results after the exam is over. You can imagine homework from ministry of Education and culture on the national curriculum. The complex case faced by Indonesia today is the location of Indonesia. Geographically, the Eurosasia and pacific plates are surrounded by active volcanoes. For this reason language learning is preferably related to the literature of children with the teaching method of copy by master creative writing.   Keywords: Elementary School, Natural Disaster, Copy By Master, 21st Century Challenge